Writing for results - Johnson, Dorothy R.; Caldwell, Sara Coover; Shreve, Daniel L.; Cambridge Educational; Morion Masters, Inc. ([New Jersey] : Cambridge Research group, Ltd. and Morion Masters, Inc., 1991)
This program stresses that good writing skills are critical to job success and that employers seek job applicants who have these skills
Title from title screen
Executive producer, Edward T. gardner ; editors, Daniel L. Shreve, Stephen R. Utt ; graphic, Stephen R. Utt
Keywords: Writing; Business writing -- Study and teaching; Report writing -- Study and teaching